Como me siento? = How do I feel? - Cote, Pamela; American Heritage Publishing Company (Boston : Houghton Mifflin Harcourt, 2001)
Words in English and Spanish describe different feelings of youngsters.
Cover title.
On board pages.
Parallel text in English and Spanish.
Keywords: Vocabulary -- Juvenile literature; Spanish language -- Glossaries, vocabularies, etc. -- Juvenile literature; English language -- Glossaries, vocabularies, etc. -- Juvenile literature; Emotions in children -- Juvenile literature; Emotions; Spanish language materials -- Bilingual; Board books